Paradigmatic perspective for development of an educational programme to facilitate critical thinking of student nurses in Namibia - Pretorius, Louise; Van Dyk, Agenes; Small, Louis; Amukugo, Hans Justus (International Journal of Advanced Nursing Studies, 2016)
This research paper is focuses on describing the paradigmatic perspective used for development of an educational programme to facilitate critical thinking of student nurses. The study of this nature requires a paradigmatic perspective this is a collection of logically linked concepts and propositions that provide a theoretical perspective or orientation that tends to guide the research approach to a specific direction.The study was conducted in four phases, beginning with the needs assessment in phase 1 through which the researcher determine the needs of the students in terms of critical thinking, followed by phase 2 on the development of an educational framework and phase 3 and 4 on implementation and evaluation and this two phases were conducted simultaneously.The positivistic paradigm allows the researcher to be orderly and disciplined in the procedures followed during the study to acquire information. For this study the researcher worked according to a specific and logical plan of action and conducted the research in a series of steps. In this study the paradigm consisted meta-theoretical such as ontological, epistemological, axiological and methodological assumption. The theoretical basis of this study included the principal of adult learning; Model of curriculum development; Nicholas and Nichols; Viedebeck’s model of teaching critical thinking and Theoretical principle of constructivism. These theoretical frameworks were applied in respectively in the phases listed above.